Linear programming: convergence of the long-pass primal-dual algorithm by the barrier function method - Luna Valdez, Juan (2021)
In this work we will try to develop and describe the primal-dual interior point method to solve the linear programming problem. This method is characterized by using barrier functions, for the primal problem and for the dual and thus deduce the primal-dual nonlinear system, whose solution defines the central path of the interior point method. It is shown that the total number of iterations that it executes is of polynomial order.